The Effect of Capital Structure, Profitability, Leverage and Company Size on Company Value - Nesta, Kelvin Andrean; Amir, Amir (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2023)
Study This aim For test influence capital structure, profitability, leverage and size company to mark company . Population study is company non - cyclical consumers listed on the Indonesia Stock Exchange (IDX) in 2019-2021. Method election sample use purposive sampling technique with the number of sample data is 168. Data analysis uses analysis multiple linear regression . Research results find proof that capital structure and profitability influential positive to mark company , meanwhile influential leverage negative to mark company as well as size company No influential to mark company.